2020
DOI: 10.1093/jxb/eraa097
|View full text |Cite
|
Sign up to set email alerts
|

The WRKY53 transcription factor enhances stilbene synthesis and disease resistance by interacting with MYB14 and MYB15 in Chinese wild grape

Abstract: Resveratrol is notable not only for its functions in disease resistance in plants but also for its health benefits when it forms part of the human diet. Identification of new transcription factors helps to reveal the regulatory mechanisms of stilbene synthesis. Here, the WRKY53 transcription factor was isolated from the Chinese wild grape, Vitis quinquangularis. Vqwrky53 was expressed in a variety of tissues and responded to powdery mildew infection and to exogenous hormone application. VqWRKY53 was located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 89 publications
0
37
0
Order By: Relevance
“…We then used a yeast one-hybrid (Y1H) assay to examine the ability of VqMYB154 to bind to these motifs. VqMYB14 and VqMYB15 from Danfeng-2, which have been proven to promote the expression of STS genes 50 , were used for comparison. The results indicated that VqMYB154 is able to bind to the L5-box and AC-box motifs but not the MYBCORE motif, which is consistent with the results for VqMYB14 but not VqMYB15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then used a yeast one-hybrid (Y1H) assay to examine the ability of VqMYB154 to bind to these motifs. VqMYB14 and VqMYB15 from Danfeng-2, which have been proven to promote the expression of STS genes 50 , were used for comparison. The results indicated that VqMYB154 is able to bind to the L5-box and AC-box motifs but not the MYBCORE motif, which is consistent with the results for VqMYB14 but not VqMYB15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the accumulation of resveratrol induced by biotic and abiotic stresses, such as pathogen attack and plant hormones, has been demonstrated by many studies (Belhadj et al, 2008;Schnee et al, 2008;D'Onofrio et al, 2009). WRKY, MYB, bZIP, and ERF transcription factors have been involved in regulating STS genes to increase the resveratrol content (Riccio et al, 2020;Wang et al, 2020). In addition, PRXs genes also have been reported to participate in regulating stilbene synthesis (Park et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Three WRKY transcription factor genes are present among the common MYB14/MYB15 HCTs. WRKY TFs have been suggested as co-regulators of MYB action in the control of STS expression [ (Wang et al, 2020), (Xi et al, 2014), (Xu et al, 2019)]. In fact, WRKY03 is bound by both TFs and supported in all three MYB14-, MYB15-and WRKY03-aggGCCNs.…”
Section: High Confidence Targets Integrated From Agggccns and Dap-seqmentioning
confidence: 99%
“…In fact, at least nine WRKY transcription factor genes are present among the common MYB14 /15 HCTs. WRKY TFs have been suggested as MYB co-regulators in the control of STS expression [ (Wang et al, 2020), (Xi et al, 2014), (Xu et al, 2019)] and also in many plant defence responses to pathogens. Particularly, WRKY03 is bound by both TFs and present in MYB14 and MYB15 leaf and fruit GCNs.…”
Section: Shared and Exclusive Regulatory Features Of S2 Myb Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation